2021
DOI: 10.1021/acs.inorgchem.0c03254
|View full text |Cite
|
Sign up to set email alerts
|

Fluoridation of HfO2

Abstract: Fluoridation of HfO2 was carried out with three commonly used solid-state fluoridation agents: PVDF, PTFE, and NH4HF2. Clear and reproducible differences are observed in the reaction products of the fluoropolymer reagents and NH4HF2 with the latter more readily reacting in air. Strong evidence of distinct, previously unreported hafnium oxyfluoride phases is produced by both reactions, and efforts to isolate them were successful for the air-NH4HF2 reaction. Synchrotron XRD, 19F NMR, and elemental analysis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The intensity of the supercell reflections was much weaker than the intensity of the subcell reflections (see Figure a). Given the small contrast of the atomic structure factors between oxygen and fluorine, 19 F NMR spectroscopy was used to directly probe the number of fluorine sites and their local crystallographic environment. The spectra are consistent with a local ratio of O:F = 1:5 in each Ti L 6 ( L = O, F) octahedron (see the following 19 F NMR discussion). This is also supported by charge balance considerations of the compound.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of the supercell reflections was much weaker than the intensity of the subcell reflections (see Figure a). Given the small contrast of the atomic structure factors between oxygen and fluorine, 19 F NMR spectroscopy was used to directly probe the number of fluorine sites and their local crystallographic environment. The spectra are consistent with a local ratio of O:F = 1:5 in each Ti L 6 ( L = O, F) octahedron (see the following 19 F NMR discussion). This is also supported by charge balance considerations of the compound.…”
Section: Resultsmentioning
confidence: 99%
“…However, since the halogen species are slowly released under basic conditions [26,27] or upon spontaneous oxidative degradation of the MXenes, [28][29][30][31] the presence of halogen terminations can limit the expandability of MXenes toward applications in semiconductor electronics and biomedical devices. For example, trace amounts of fluorine species, due to their strong reactivity, can degrade device components such as gate oxides [32][33][34] or metal electrodes, [35] leading to the device failure over longterm use. More importantly, for their sustainable use on biological interfaces, [36][37][38] fluorinated MXenes can raise safety concerns because the transudation of fluoride ions can be toxic to living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…15−20 Flynn et al reported the fluoridation of HfO 2 using PVDF, PTFE, and NH 4 HF 2 as solid-state fluoridation agents, which afforded either single-phase or multiple-phase hafnium oxyfluorides, respectively. 15 tion method has only been reported in limited several oxyfluoride systems until now. Further exploration and precise fluorination syntheses are needed for more functional metal oxyfluorides.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature fluorination using metal oxides as raw materials is one of the typical methods. NH 4 HF 2 , polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE) are commonly used as the fluoridation agents in this method. Flynn et al reported the fluoridation of HfO 2 using PVDF, PTFE, and NH 4 HF 2 as solid-state fluoridation agents, which afforded either single-phase or multiple-phase hafnium oxyfluorides, respectively . Hirai et al.…”
Section: Introductionmentioning
confidence: 99%